Question
upstudy study bank question image url

Given \( h(x)=\left(\frac{1}{s}\right)^{x} \) 7.3.1 Determine the equation of \( x-1(x) \), the inverse of \( h \), in the forn \( y=\ldots \) 7.3.2 Describe the transformation from, 8 to \( h \). i

Ask by Tyler Donnelly. in South Africa
Feb 18,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

7.3.1 The inverse of \( h(x) \) is \( h^{-1}(x) = \frac{\ln(x)}{\ln(1/s)} \) or \( h^{-1}(x) = -\frac{\ln(x)}{\ln(s)} \) or \( h^{-1}(x) = -\log_{s} x \). 7.3.2 The function \( h(x) = \left(\frac{1}{s}\right)^x \) is obtained from \( f(x) = s^x \) by reflecting its graph across the y-axis.

Solution

We are given the function   h(x) = (1/s)^x. Below are the steps to solve each part. ────────────────────────────── 1. Inverse Function of h(x) To find the inverse function, h⁻¹(x), we start with   y = (1/s)^x. Step 1. Interchange x and y (since the inverse “swaps” the roles of the input and output):   x = (1/s)^y. Step 2. Solve for y. To do so, take the natural logarithm on both sides:   ln(x) = ln((1/s)^y). Step 3. Use the logarithm power rule (ln(a^b) = b·ln(a)):   ln(x) = y · ln(1/s). Step 4. Solve for y:   y = ln(x) / ln(1/s). Thus, one acceptable form for the inverse is   h⁻¹(x) = ln(x) / ln(1/s). An equivalent form can be obtained by recalling that ln(1/s) = –ln s. Therefore, we may also write   h⁻¹(x) = –ln(x)/ln(s). Yet another equivalent way to express the answer is to use logarithms with base s:   h⁻¹(x) = –logₛ x. ────────────────────────────── 2. Transformation from the Base Exponential to h(x) Observe that   h(x) = (1/s)^x = s^(–x). This means that h(x) is obtained from the usual exponential function f(x)=s^x by replacing x with –x. Geometrically, replacing x with –x reflects the graph about the y-axis. In summary, the transformation from the graph of f(x)=s^x to the graph of h(x)=s^(–x) is:   • A reflection across the y–axis. ────────────────────────────── Final Answers 7.3.1 The inverse of h(x) is   h⁻¹(x) = ln(x) / ln(1/s)    or  h⁻¹(x) = –ln(x)/ln(s)  or  h⁻¹(x) = –logₛ x. 7.3.2 The function h(x) = (1/s)^x is obtained from f(x)=s^x by reflecting its graph in the y-axis (i.e. replacing x with –x).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To find the inverse of \( h(x) = \left(\frac{1}{s}\right)^x \), we start by setting \( y = h(x) \). This gives us \( y = \left(\frac{1}{s}\right)^x \). To solve for \( x \), we take the logarithm of both sides: \[ x = \log_{\frac{1}{s}}(y). \] Thus, the equation of the inverse function \( h^{-1}(x) \) can be expressed as: \[ y = \log_{\frac{1}{s}}(x). \] Now, regarding the transformation from \( y = 8 \) to \( h \), we notice that \( h(x) \) represents an exponential decay function due to the base being \( \frac{1}{s} \). Transitioning from the horizontal line \( y = 8 \) to the decay curve of \( h(x) \) involves a vertical shift downwards. Thus, where the horizontal line intersects will reflect into a point on the curve, as the exponential decay values decrease rapidly. This transformation can be visually illustrated through a graph, showing how the constant value \( 8 \) is lowered by the effect of the decreasing exponential function.

Latest Pre Calculus Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy